Revitalisasi Kearifan Lokal dalam Masyarakat Multikultural di Kecamatan Lingsar, Lombok Barat, NTB - Ahmad Sodli (Analisa: Journal of Social Science and Religion, 2010)
This study focuses on topat war which exists in Lingsar sub District West Lombok. This tradition still becomes guidance for the residents. Questions of this research are, how the revitalization of local tradition named topat war is empowered by communities as a way to integrate them, and what are the supporting factors of it? This is a qualitative research. Data were gathered using interview, observation, and documentary research. Result of this study depicts that there are many steps of topat war, namely cleaning of holy weapons and hereditary articles, making tetaring, a tent made of coconut leaf and bamboo, remember day of the death of KH. Abdul Malik, KH. Abdul Rouf, and Hj. R. Ayu Dewi Anjani, remembering the way of KH.Abdul Malik, slaughtering buffalo for dish service, conducting topat war. This topat war has been seen as a way of community’s integration in many aspects, for instance in remembering the way of KH.Abdul Malik, animal used, and the origin of topat. This tradition has been guarded because  it is a way to glue harmony among believers. Keywords : Tradition, Topat War, Religius, Harmony